They Do Things Differently There. Essays on Cultural History - Johnson, Bruce; Kiiskinen, Harri (eds.) (fi=Turun yliopisto|en=University of Turku|, 2015)
This collection of Finnish essays in cultural history will be revelatory for anglophone readers. Pioneering in the study of cultural history as early as the nineteenth century, by the 1930s Finnish scholars already deployed the broad conception of 'culture' as embracing 'everyday life' that is usually thought of as emerging in the work of Raymond Williams decades later. These essays emanate from the Department of Cultural History, established at the University of Turku in 1972, and its partner department at the University of Lapland. The collection signals new genealogies of cultural historiography in general, and in its distinctively Finnish inflections.